A phonological comparison on Akha and Hani - Hansson, Inga-Lill (2024)
The main material for the study of Hani has been the wordlist provided l!d/Dai in 1964, used extensively by David Bradley in his "Akha and Southern Loloish" and "Proto-Loloish". Recently some more material on Ilani became available to me, consisting of a Hani-Chinese Wordlist, Kunming, 1959, 108 p., and a tape-recording of 288 Hani words, spoken by a Hani from Ytinnani.